Interpretive problems in a search for micro-invertebrate fossils from a Neoproterozoic limestone in Namibia - Brain, C K; Hoffman, K -H; Prave, A R; Fallick, A E; Coetzee, J; Botha, A J (Bernard Price Institute for Palaeontological Research, 2001)
Attention is focussed on a carbonate sequence in the Auros Formation of the Otavi Group in northern Namibia, where several limestone layers are found to have been phosphatised. These contain an abundance of unusual objects, some of which suggest sponge-like microfossils, whereas others superficially resemble bivalved shells. Alternatively they may be pseudofossils - the deceptive products-of a phosphatisation process and subsequent diagenetic effects in the limestone. Since this deposit antedates the ca. 590 million-year-old Ghaub or Marinoan glaciation, the presence of any potential metazoan fossils is worth investigating. The objects in question are described and alternative interpretations are discussed.
Keywords: Neoproterozoic; Otavi Group; microfossils; pseudofossils